New insights on the origin of troctolites from the breakaway area of the Godzilla Megamullion (Parece Vela back‐arc basin): The role of melt‐mantle interaction on the composition of the lower crust. (24th February 2016) - Sanfilippo, Alessio; Dick, Henry J. B.; Ohara, Yasuhiko; Tiepolo, Massimo
Abstract: The troctolites and olivine‐gabbros from the Dive 6 K‐1147 represent the most primitive gabbroic rocks collected at the Godzilla Megamullion, a giant oceanic core complex formed at an extinct spreading segment of the Parece Vela back‐arc basin (Philippine Sea). Previous investigations have shown that these rocks have textural and major elements mineral compositions consistent with a formation through multistage interaction between mantle‐derived melts and a pre‐existing ultramafic matrix. New investigations on trace element mineral compositions basically agree with this hypothesis. Clinopyroxenes and plagioclase have incompatible element signatures similar to that of typical‐MORB. However, the clinopyroxenes show very high Cr contents (similar to those of mantle clinopyroxene) and rim having sharply higher Zr/REE ratios with respect to the core. These features are in contrast with an evolution constrained by fractional crystallization processes, and suggest that the clinopyroxene compositions are controlled by melt‐rock interaction processes. The plagioclase anorthite versus clinopyroxene Mg#[Mg/(Mg + Fe Tot )] correlation of the Dive 6 K‐1147 rocks shows a trend much steeper than those depicted by other oceanic gabbroic sections. Using a thermodynamic model, we show that this trend is reproducible by fractionation of melts assimilating 1 g of mantle peridotite per 1 °C of cooling. This model predicts the early crystallization of high Mg# clinopyroxene, consistent with our petrological observation. The melt‐peridotite interaction process produces Na‐rich melts causing the crystallization of plagioclase with low anorthite component, typically characterizing the evolved gabbros from Godzilla Megamullion. Abstract : The Dive 6K‐1147 troctolites and olivine gabbros are formed through a process of interaction between melts and the shallow mantle section. Thermodynamic models show that this can reproduce the steep An in plagioclase versus Mg# in clinopyroxene correlation depicted by these rocks. This explains the occurrence of evolved gabbros with low An plagioclase, typically characterizing the lower crust at Godzilla Megamullion.